Barragistas na rede: construção de memória e identidade nas redes sociais - Pequito, Lurdes (Trabalhos de Antropologia e Etnologia, 2020)
In the 1950s, in a context of defense of industrialization as a factor of development and progress, three dams were built for the hydroelectric exploitation of the Douro River. Thousands of workers came from other dams and mines. Picote was the first, inaugurated in 1958, followed by Miranda and Bemposta. A comparative study of two internet pages related to the group of workers (Facebook – Barragistas do Douro and institutional page of EDP-REN) is carried out in order to identify processes of memory and forgetfulness in the construction of barragista identity. These processes are analyzed based on the representations and narratives about home and energy. These two pages are compared, looking for connections between the own discourse of the networks and the production of other objects of memory.